Kolej Ibukota Kinabalu web site / Ahmad Naim Aminnudin - Aminnudin, Ahmad Naim (2003)
This thesis presents a web site development for Kolej Ibukota Kinabalu (KIK), which should further strengthen its marketing strategy, which automatically enhance its long-term competitiveness in education field in our country. The findings reported in this thesis would lead to the conclusion that KIK is searching for a better marketing strategy in the way to promote the college name and also to find an effective way to distribute the application form. This comes from the fact that many established universities and colleges in Sabah area are already offering comparable value-added services to its students through similar or different service features. Apart from offering similar and substitute programs, these private colleges and universities are also nearer to their respective customers' geographical area, making KIK's offering as less attractive to the prospective students. After taking in account KIK's present problems, development of a web site should help to overcome the situations. The web site features the college bulletin board, online application form, forum and administration interface. Therefore, with the development of the web site, it will produce various effective and efficient communication and information distribution among the Internet user, potential students and KIK students. Thus, it will also increase the work performance among KIK staffs.